"Don't stop believing!" From health religiosity to an equality-enhancing hermeneutic of health promotion. (4th June 2018) - Pelters, Britta; Roxberg, Åsa
ABSTRACT: Purpose : Health beliefs are usually regarded as subjective understandings of one's health. They can, however, be re-interpreted by drawing on the understanding that the structural features of the health discourse resemble the characteristics of a religion and on the spiritual dimension of health with its possibly salutogenic influence. The applicability of the notion of "health religiosity" and its consequences for individual health promotion are explored. Method : Data consist of already existent semi-structured interviews. These have been reanalyzed in a deductive-hermeneutical way by using a five-dimensional concept of religiosity as deductive template. Results : The concept of religiosity proved to be productive and revealed that all health dimensions in the case are infused with spiritually ennobled ideas. Conclusion : We conclude that, irrespective of their factual accuracy, the salutogenic potential of ennobled ideas may best be utilized by understanding them hermeneutically. An exploration of a narrative hermeneutic approach to individual health promotion is suggested as the merging of meaning horizons in a hermeneutic dialogue is expected to increase awareness of spiritualized aspects of health beliefs. This may mitigate healthism and health disparities. Moreover, three challenges for individual health promotion are anticipated: realizing the situation, recognizing its complexity and resisting a simplistic practical approach.